Targeting AMP-activated protein kinase in sepsis - Yumoto, Tetsuya; Coopersmith, Craig M. (Frontiers in Endocrinology, 2024)
Sepsis is a global health challenge marked by limited clinical options and high mortality rates. AMP-activated protein kinase (AMPK) is a cellular energy sensor that mediates multiple crucial metabolic pathways that may be an attractive therapeutic target in sepsis. Pre-clinical experimental studies have demonstrated that pharmacological activation of AMPK can offer multiple potential benefits during sepsis, including anti-inflammatory effects, induction of autophagy, promotion of mitochondrial biogenesis, enhanced phagocytosis, antimicrobial properties, and regulation of tight junction assembly. This review aims to discuss the existing evidence supporting the therapeutic potential of AMPK activation in sepsis management.